Ontología literaria posthumana: escrituras, agencias y disputas en la era de la IA - Maguiño, Miguel Hugo (2025)
This text examines how literature, historically shaped by the technologies of its time—orality, writing, printing, digital media—is currently undergoing a profound transformation with the emergence of artificial intelligence (AI). This not only alters practices but also redefines literary ontology: it decenters the author, turns style into an adjustable parameter, and transforms the reading experience into collective interaction and validation. It addresses classic problems of authorship from Foucault and Barthes, now challenged by distributed human-machine authorship, as well as the algorithmic fusion of styles and posthuman creativity. Literature takes on new forms of existence—transmedia, fragmentary, fluid—and proposes categories such as collaborative work, textuality without a subject, and reading without a biography. What endures—author, style, experience, reading, canon—is reconfigured under algorithmic and community-based criteria, displacing traditional criteria with metrics of virality. For literary theory, three urgent lines of action are required: incorporating machinic agency, redefining the status of the text, and expanding categories of analysis toward technical notions such as "prompt" or "generation temperature." The essay concludes that the challenge is not to preserve old categories, but to rethink them, training readers and critics capable of engaging with a hybrid literary ecosystem where humans and machines co-create meaning.